2021
DOI: 10.3390/app11062798
|View full text |Cite
|
Sign up to set email alerts
|

3D Cavitation Shedding Dynamics: Cavitation Flow-Fluid Vortex Formation Interaction in a Hydrodynamic Torque Converter

Abstract: Recent experiments have shown interactions between the cavitation and fluid vortex formation in a hydrodynamic torque converter. This study aimed to clarify the unsteady cavitation trigger mechanism and flow-induced vibration caused by turbulence–cavitation interactions. The mass transfer cavitation model and modified Reynolds-averaged Navier–Stokes k–ω model were used with a local density correction for turbulent eddy viscosity to investigate the cavitation structure in a hydrodynamic torque converter under v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The nominal torque of the pump M Bg , refers to the torque absorbed by the pump when its speed is equal to 1000 r/min in the torque section of the traction condition area. The parameter κ represents the pump capacity factor of the torque converter at a specific SR [15].…”
Section: Definition Of Torque Converter Parametermentioning
confidence: 99%
“…The nominal torque of the pump M Bg , refers to the torque absorbed by the pump when its speed is equal to 1000 r/min in the torque section of the traction condition area. The parameter κ represents the pump capacity factor of the torque converter at a specific SR [15].…”
Section: Definition Of Torque Converter Parametermentioning
confidence: 99%
“…The key to cavitation simulation is to establish a proper cavitation model [19] which governs the transformation between liquid and vapor. The cavitation phenomenon of hydraulic torque converter was studied based on the Zwart cavitation model in this paper [11,13,20,21].…”
Section: Cavitation Modelmentioning
confidence: 99%
“…Zhao et al [10] studied the mechanism of bubble breakup in the hydraulic torque converter numerically by implanting bubbles in it. Guo et al [11,12] and Ran et al [13] investigated the evolution of transient cavitation in the torque converter, and the results indicated that cavitation mainly occurred in the stator, and severely reduced the performance of the torque converter. Liu et al [14][15][16] studied the influence of stator blade shape on the cavitation process of a torque converter and found out that cavitation was directly affected by internal mass flow rate, which they then improved the torque converter design considering the presence of cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al [12] numerically simulated the cavitating evolution of the angular nozzle and optimized the shape of the nozzle using the RNG k−ε model. Ran et al [13] used the modified Reynoldsaveraged k−ω model to simulate the cavitating morphologies in the hydrodynamic torque converter for different working conditions. However, due to the restraints of the used model, the RANS method can only simulate the time-averaged flow, and cannot accurately predict the spatial and temporal evolution of a cavitating cloud.…”
Section: Introductionmentioning
confidence: 99%